EVALUATING THE UNDERSTANDING OF SOCIAL CONSTRUCTIVISM AMONG PRE-SERVICE TEACHERS AT INSTITUT PENDIDIKAN GURU, KAMPUS KENINGAU, SABAH - Muhammad Naufal Bin Abbas; Emmi Binti Joking; Edna John; Sabriah Binti Maili @ Mohd Rasli; Doti Bin Asing (Jurnal Penyelidikan Sains Sosial, 2023)
The present study, which was conducted at IPGK Keningau, assessed the comprehension of social constructivist techniques among pre-service teachers. These techniques emphasize collaborative learning and knowledge acquisition through social interactions. The study included participants from various academic years, allowing for a comprehensive analysis of their comprehension levels. The study included participants from several academic years, allowing for a comprehensive analysis of their comprehension levels at different phases of their educational progression. After the data was collected, the raw scores were transformed into percentage values. The average score across all academic years was 74.38%, indicating a good level of understanding of social constructivist principles. However, discrepancies were observed across different school years, with factors such as cohort size affecting these variations. The study concluded that pre-service teachers have shown commendable comprehension of social constructivist approaches, but discrepancies across different academic years call for a more thorough investigation. The results emphasize the need for a similar instructional approach throughout all academic years to promote consistent understanding and application of these essential educational principles.